IMPLEMENTING R5 AND KIVA IN WAREHOUSE MANAGEMENT A CASE EXAMPLE FOR SPAR IKEJA, NIGERIA - Justin Ogala S. EGBUNU (Modern Management Review, 2025)
The logistics of any superstore chain is its ability to get the products at the shelves which their customers really want. The SPAR Nig ltd is a limited liability company operating in Nigeria under license from its South Africa conglomerate whose franchise was given to do the business in Nigeria. Considering that it has been able to meet the high customer flow, thus, need for reliable and unadulterated goods and products, SPAR has developed a warehouse within its superstore chain’s location. The goods are kept and restocked on shelf as the replenishment is required on no advance Warehouse Management System. The aim of this paper is to analyze the replenishment technique for goods efficiently and effectively while using less hazardous methods and reduce the traffic of high end machinery like forklift moving product inside the control space. The method analysis using CAM methodology will employ a small AGV simulated system requested by shelve pickers and run the simulation of product to the pickers with minimal walk around following the nodes path outline on the floor bowl. This will implicitly create a refined work for staff and introduce technology to solve related issues/ergonometric enhancement for employees while promoting the speed of shelf replenishment.